P-629 A prospective, randomized, placebo-controlled pilot trial investigating telomere length dynamics and ovarian function in patients with diminished ovarian reserve (DOR) after danazol treatment. (30th June 2022) - Oriz, I. Córdova; Toribio, M; Khols, G; Iglesias, C; Chico-Sordo, L; Polonio, A.M; Medrano, M; Díaz-Gómez, M; Molinero-Ballesteros, A; Meseguer, M; García-Velasco, J.A; Varela, E
Abstract: Study question: Could the administration of a synthetic steroid -danazol- for 3 months reactivate telomerase activity and lengthen telomeres in patients with DOR? Summary answer: Danazol treatment resulted in an increase of the mean leukocyte telomeric length (TL) but did not improve fertility results after the nearest ovarian stimulation (OS). What is known already: A primary molecular cause of aging is telomere attrition, given that the accumulation of critically short telomeres leads organ dysfunction. Telomere shortening can be counteracted by the telomerase enzyme, which is responsible for adding deoxyribonucleotides to the linear ends of chromosomes. In patients with DOR, TL in granulosa cells (GCs) is short and telomerase activity is absent, compromising their proliferative capacity. Previuos studies have shown that estrogens can activate telomerase gene transcription through estrogen-responsive elements located in the promoter of the telomerase gene. Therefore, telomere attrition could be reduced in patients with DOR upon telomerase reactivation. Study design, size, duration: This blinded, placebo-controlled pilot trial was carried out at IVIRMA Madrid clinic between February 2020 and February 2022. The study included 12 patients with DOR (AMH<2ng/ml) which were randomized to danazol or placebo. Patients had 12 visits for health supervision and in vitro fertilization (IVF) treatment. Both groups received danazol (400mg per day) or placebo for 3 months. As control group, 7 patients with normal ovarian reserve (AMH≥2ng/ml) were included. Participants/materials, setting, methods: In both groups, blood samples were collected prior (PT) and after the treatment (AT). Luteinized GCs and blood samples were obtained during oocyte retrieval, after OS. Leukocytes were purified in Ficoll gradients and then, evaluated for TL and TRF1 levels by Quantitative Fluorescent in Situ Hybridization followed by image acquisition using high resolution confocal microscope. IVF parameters were assessed according to IVIRMA standard protocols. Main results and the role of chance: A total of 19 women were recruited: 5 in the placebo group (39.8±2.7 years), 7 in Danazol group (41.0±3.0 years) and 7 in control group (39.5±3.0 years). The Danazol group showed a trend to higher mean TL in leukocytes after the treatment (108.2±37.4 versus 99±13.2 a.u., AT vs PT). Interestingly, the percentage of long telomeres also increased with treatment (15.5±0.0 versus 10.8±8.1 a.u., AT vs PT). In addition, there was a decrease of the percentage of critically short telomeres (15.7±0.0 versus 20.8±9.9 a.u. AT vs PT). In the placebo group, mean leukocyte TL and the percentage of long and short telomeres remained constant. These findings suggest that telomeres lengthen after Danazol treatment. The protein levels of TRF1, a shelterin involved in telomere protection, were similar in both Danazol and placebo groups. Regarding fertility, there were no differences in the number of antral follicles, total and MII oocytes, fertilization rate and blastocyst formation. The control group had, as expected, signficantly higher mean follicle number after OS when compared with Danazol (16.0±1.4 and 0.7±0.9, P < 0.0001) and placebo (16.0±1.4 and 5.0±3.8, p = 0.0127) groups, and higher numbers of total oocytes retrieved (p = 0.006; control and Danazol, and p = 0.007; control and placebo). Limitations, reasons for caution: Firstly, the number of patients included in the study is limited due to strict inclusion/exclusion criteria. Secondly, because follicle growth can take up to 150 days, danazol effects could be noticeable at later OS and not only in the first OS, which was the only one studied here. Wider implications of the findings: Since telomeres seem to elongate in blood samples after Danazol treatment in DOR patients, we could hypothesize that this may have a positive impact for general health, including the ovaries. Thus, danazol therapy might help improving IVF outcomes, perhaps at later OS. Trial registration number: NCT04058678